An assistant for group formation in CSCL based on constraint satisfaction - Bais, Juan (2013)
Group formation is a key aspect in computer-supported collaborative learning, since different characteristics of students might influence the group performance. In this article, we present an assistant that models group formation as a weighted constraint satisfaction problem (WCSP), and considers three students’ features, namely: psychological styles, team roles and social networks. Our WCSP formulation is able to combine constraints and preferences for individuals and groups. This assistant can aid teachers to form groups considering factors such as team role balance and distribution of psychological styles. We report on a pilot study to evaluate the proposal in different scenarios.